Cobalt ferrite bearing nitrogen-doped reduced graphene oxide layers spatially separated with microporous carbon as efficient oxygen reduction electrocatalyst - Kashyap, V.; Singh, S. K.; Kurungot, S. (ACS Applied Materials and Interfaces, 2016)
The present work discloses how high-quality dispersion of fine particles of cobalt ferrite (CF) could be attained on nitrogen-doped reduced graphene oxide (CF/N-rGO) and how this material in association with a microporous carbon phase could deliver significantly enhanced activity toward electrochemical oxygen reduction reaction (ORR). Our study indicates that the microporous carbon phase plays a critical role in spatially separating the layers of CF/N-rGO and in creating a favorable atmosphere to ensure the seamless distribution of the reactants to the active sites located on CF/N-rGO. In terms of the ORR current density, the heat-treated hybrid catalyst at 150 °C (CF/N-rGO-150) is found to be clearly outperforming (7.4 ± 0.5 mA/cm 2 ) the state-of-the-art 20 wt % Pt-supported carbon catalyst (PtC) (5.4 ± 0.5 mA/cm 2 ). The mass activity and stability of CF-N-rGO-150 are distinctly superior to PtC even after 5000 electrochemical cycles. As a realistic system level exploration of the catalyst, testing of a primary zinc-air battery could be demonstrated using CF/N-rGO-150 as the cathode catalyst. The battery is giving a galvanostatic discharge time of 15 h at a discharge current density of 20 mA/cm 2 and a specific capacity of ∼630 mAh g -1 in 6 M KOH by using a Zn foil as the anode. Distinctly, the battery performance of this system is found to be superior to that of PtC in less concentrated KOH solution as the electrolyte.

Multifunctional copper dimer: structure, band gap energy, catalysis, magnetism, oxygen reduction reaction and proton conductivity - Sarkar, D.; Chandra Rao, P.; Aiyappa, H. B.; Kurungot, S.; Mandal, S.; Ramanujam, K.; Mandal, S. (RSC Advances, 2016)
A new dimeric copper complex namely, [Cu2(PDA)2(Ald)2(H2O)2]·8H2O, 1, (where PDA = 2,4-pyridine dicarboxylic acid, Ald = aldrithiol) has been synthesized through a slow diffusion technique. Compound 1 is a molecular structure and assembled through H-bonding forming a supramolecular architecture. The CuO2N3 units bridged through an aldrithiol molecule to form the dimeric structure. The lattice water molecules are linked through H-bonding to form the decameric water cluster. The decameric water clusters are H-bonded to each other to form the 1D chain which resulted in excellent water stability and conduction of protons under humid conditions. Band gap energy and magnetic measurements show that compound 1 is a semiconductor and paramagnetic in nature. Further the compound is shown as a selective heterogeneous catalyst for styrene and cyclohexene epoxidation. This also shows a facile oxygen reduction reaction (ORR) and can be used as a promising Pt-free cathode in alkaline Direct Methanol Fuel Cells (DMFC). The present results suggest that compound 1 is a promising multifunctional material

All-solid-state-supercapacitor possessing a non-aqueous gel polymer electrolyte prepared using a UV-assisted in situ polymerization strategy - Vijayakumar, V.; Anothumakkool, B.; Torris, A. T. A.; Nair, S. B.; Badiger, M. V.; Kurungot, S. (Journal of Materials Chemistry A, 2017)
In this work, we report the synthesis of a high ionic conducting and mechanically stable non-aqueous gel polymer electrolyte (GPE) in which a liquid electrolyte (LiClO4/propylene carbonate) is entrapped in a poly(2-hydroxy-3-phenoxy propyl acrylate) matrix by a UV assisted in situ polymerisation strategy. Unlike conventional dry and quasi-solid non-aqueous GPEs, our system (H-P-L-3M-80%) shows an excellent ionic conductivity of 4.7 x 10(-3) S cm(-1), a value which is comparable to those of non-aqueous liquid electrolytes. The high mechanical stability of GPE arises due to the covalent cross-links present in the polymer matrix as well as the reversible non-covalent cross-links between the solvent and the polymer matrix through the Li+ cations. Subsequently, the GPE has been prepared in situ on the inner and the outer surface of the electrode material to fabricate a 2.0 V supercapacitor device with a high mass loading (3.8 mg cm(-2)) of the active material (YP-80F, a high surface area porous carbon). The device shows an equivalent series resistance (ESR) as low as 2.2 Omega, which is close to that of the device fabricated from the corresponding liquid electrolyte and is far better than those of the devices evolved from conventional GPEs and dry polymer electrolytes. The mass specific capacitance of 113 F g(-1) obtained at a current density of 2 mA cm(-2) shows 81% retention even at a high current density of 20 mA cm(-2). The scalability of the strategy is demonstrated by fabricating a large area (area = 16 cm(2), loading = 4.0 mg cm(-2)) all-solid-state flexible-supercapacitor (H-P-L-3M-S-4.0) device which can be operated at a potential window of 2.5 V. The device was found to show a mass specific capacitance of 111 F g(-1) at a current density of 1 mA cm(-2) (0.25 A g(-1)), all the while, retaining a very low ESR of 2.2 Omega. The potential of the strategy to mimic the liquid-like electrode-electrolyte interface, augmented with the ability to tune further, opens up new horizons for energy storage devices.

Copper oxide supported on three-dimensional ammonia-doped porous reduced graphene oxide prepared through electrophoretic deposition for non-enzymatic glucose sensing - Maaoui, H.; Singh, S. K.; Teodorescu, F.; Coffinier, Y.; Barras, A.; Chtourou, R.; Kurungot, S.; Szunerits, S.; Boukherroub, R. (Electrochimica Acta, 2017)
The paper reports on the preparation of N-doped porous reduced graphene oxide/copper oxide (ammonia-doped-prGO/CuO) nanocomposite on gold electrodes using electrophoretic deposition (EPD) from an ethanolic suspension of ammonia-doped-prGO and Cu(ClO4)(2) by applying a DC voltage. The ammonia-doped-prGO/CuO nanocomposite film thickness is controlled by varying the deposition time. Morphological analysis using scanning electron microscopy (SEM) showed the formation of a 3 dimensional structure with CuO nanoparticles being homogeneously embedded in the graphene layer. Xray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman analysis revealed that the deposited copper was in its oxidized form, mainly CuO. The Au/ammonia-doped-prGO/CuO electrode was successfully applied for non-enzymatic amperometric detection of glucose. Under optimized conditions, the electrode exhibited a sensitivity of 1210 mu mM(-1) cm(-2) with a detection limit of 0.25 p,M (S/N =3) over a wide concentration range (0.25 mu M to 6 mM) at an applied potential of +0.50 V vs. Ag/AgCl. The electrode material displayed good stability, excellent selectivity, and accurate measurement in healthy and diabetic human serum samples.

N-doped porous reduced graphene oxide as an efficient electrode material for high performance flexible solid-state supercapacitor - Singh, S. K.; Dhavale, V. M.; Boukherroub, R.; Kurungot, S.; Szunerits, S. (Applied Materials Today, 2017)
Supercapacitors (SCs) are energy storage devices with an immense potential to resolve energy related issues. Being a low cost, durable and multifunctional material, graphene and its derivatives are the most promising candidates for SCs. Here, we report the synthesis of N-doped porous reduced graphene (N-pGr) and its use for the fabrication of all-solid-state supercapacitor (ASSC) device. The N-pGr exhibited a specific capacitance of 230 F g(-1) at 1 A g(-1) current density and good capacitance retention up to 88% even after 10,000 galvanostatic charge-discharge cycles recorded at 5 A g(-1) fabricated in a solid-state supercapacitor. The synergistic effect of the porosity and N-doping is believed to be the underlying principle for the improved charge storage ability when compared to other reports. Significantly, the porous nature of N-pGr contributes in increasing the electroactive surface area for the formation of electrical double layer as well as facilitating the faster movement of electrolyte ions inside the electrode network. N-doping is believed to change the electrical properties of the electrode material and also to participate in the pseudo-capacitance which helped to boost the overall capacitance of the fabricated device. The good capacitance retention provides the room for making robust flexible solid-state supercapacitor (FSSC) with the N-pGr material.

Bifunctional oxygen reduction and evolution activity in brownmillerites Ca2Fe(1- x)CoxO5 - Thundiyil, S.; Kurungot, S.; Devi, R. N. (ACS Omega, 2019)
State-of-the-art catalysts for oxygen reduction and evolution reactions (ORR and OER), which form the basis of advanced fuel cell applications, are based on noble metals such as Pt and Ir. However, high cost and scarcity of noble metals have led to an increased demand of earth-abundant metal oxide catalysts, especially for bifunctional activity in ORR and OER. The fact that Pt and Ir or C, the cost-effective alternatives suggested, do not display satisfactory bifunctional activity has also helped in turning the interest to metal oxides which are stable under both ORR and OER conditions. Brownmillerite A2B2O5 type oxides are promising as bifunctional oxygen electrocatalysts because of intrinsic structural features, viz., oxygen vacancy and catalytic activity of the B-site transition metal. In this study, Co-doped Ca2Fe2O5 compounds are synthesized by the solid state method and structurally analyzed by Rietveld refinement of powder X-ray diffraction data. The compound Ca2Fe2O5, crystallizing in the Pcmn space group has alternative FeO4 tetrahedral and FeO6 octahedral layers. Its Co-doped analogue, Ca2Fe1.75Co0.25O5, also crystallizes in the same space group with both tetrahedral and octahedral Fe positions substituted with Co. However, Ca2FeCoO5 in the Pbcm space group shows interlayer ordering with Co-rich octahedra connected to Fe-rich tetrahedra and vice versa. Oxygen bifunctional activities of these catalysts are monitored by rotating disc electrode and rotating ring disc electrode techniques in alkaline media. A close analysis of the ORR and OER was conducted through comparison of various parameters such as onset potential, current density, halfwave potential, and other kinetic parameters, which suggests that the presence of Co in the B site aids in achieving better bifunctional activity and bulk conductivity. In addition, Co(II)/Co(III) redox systems and their comparative concentrations also play a decisive role in enhancing the activity.

Rylene diimide-based alternate and random copolymers for flexible supercapacitor electrode materials with exceptional stability and high power density - Sharma, S.; Soni, R.; Kurungot, S.; Asha, S. K. (Journal of Physical Chemistry C, 2019)
Donor–acceptor pi-conjugated polymers are emerging as interesting electrode materials for supercapacitor device applications. They offer an exciting possibility of charge storage in both positive and negative electrodes because they are both p- and n-dopable. The ambipolar charging enables higher operating voltage, which can afford higher specific energy and power densities. The donor–acceptor design can be either donor-alternate-acceptor or donor-random-acceptor. This architectural variation has the potential to modify the charge storage; yet surprisingly not much literature data is available exploiting this aspect. This paper explores the alternate and random geometries of donor–acceptor π-conjugated polymers based on naphthalene diimide or perylene diimide (PDI) as the acceptor component and benzodithiophene (BDT) as the donor component and their application as composite electrode materials in a type III supercapacitor device. Results show that the donor–acceptor alternate design involving P(PDI-alt-BDT) is an excellent supercapacitor electrode material with specific capacitance of 113 F g–1 with excellent stability up to 4000 cycles and almost 100% retention of the initial capacitance in a single-electrode setup in a PC-LiClO4 organic electrolyte. A flexible supercapacitor device was also fabricated which shows areal capacitance of 35 mF cm–2 at a current density of 0.5 mA cm–2, which is promising for commercial applications.